Terahertz Semiconductor Dual‐Comb Sources with Relative Offset Frequency Cancellation. Issue 4 (3rd February 2023) - Li, Ziping; Ma, Xuhong; Zhou, Kang; Liu, Binbin; Wang, Chenjie; Liao, Xiaoyu; Guan, Wen; Wu, Shumin; Liu, Han; Zhang, Zhenzhen; Cao, J. C.; Li, Min; et al.
Abstract: A dual‐comb source, employing two frequency combs with a slight difference in repetition frequencies, shows unique advantages in high precision spectroscopy, imaging, ranging, communications, and so on. In the terahertz (THz) frequency range, the electrically pumped quantum cascade laser (QCL) offers the possibility of realizing a compact dual‐comb source due to its semiconductor‐based chip‐scale configuration. Although dual‐comb operation of THz QCLs has been experimentally demonstrated, a full stabilization of THz dual‐comb sources is still challenging. Here, a self‐reference method is proposed for a pure THz QCL system. Without using any external locking components, one dual‐comb line is filtered out and it is beaten with the whole dual‐comb signal, which eliminates the common carrier offset frequency noise and reduces the dual‐comb repetition frequency noise. It is demonstrated that the self‐reference technique can significantly improve the long‐term stability of the dual‐comb signal. A record "maxhold" linewidth of 14.8 kHz (60 s) is obtained by implementing the self‐reference technique, while without the self‐reference, the dual‐comb lines show a "maxhold" linewidth of 2 MHz (15 s). The method provides the simplest way to improve the long‐term stability of THz QCL dual‐comb sources, which can be further adopted for various measurements. Abstract : A self‐reference method is proposed to obtain fully stabilized terahertz semiconductor dual‐comb sources. By selecting one dual‐comb line and mixing it with the entire dual‐comb signal, the common carrier offset frequency noise can be eliminated. It is experimentally demonstrated that the technique can significantly improve the long‐term stability of the dual‐comb source, which can be further adopted for various measurements.